(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Seasonal keratoconjunctivitis of military personals in Chattogram area causes loss of many working hours with prolonged sufferings. Objective: To explore the outcome of using Ganciclovir in seasonal viral keratoconjunctivitis in Combined Military Hospital, Chattogram. Methods: This prospective study was conducted in department of ophthalmology of Combined Military Hospital (CMH), Chattogram, from January 2013 to September 2018. Diagnosis was made by clinical signs, symptoms and laboratory study of conjunctival smear to exclude bacterial or fungal cause. Initially they were treated with artificial tear and antibiotic to prevent secondary bacterial infection. After three days of complete rest, the cases presented with static or further deteriorated condition were treated with Ganciclovir eye gel five times a day for two weeks. After subsidence of acute redness, topical dexamethasone was also applied for 4 times and then 3 times at one week interval. Follow up periods were 3 days, 1 week, 2 weeks, 4 weeks and 3 months subsequently. Results: A total of 2678 cases were included in our study. About 78% of the patients were male and 22% were female. 95% patients were from age group of young and serving personnel. Ganciclovir was used in 750 (28%) cases. With conventional treatment, recovery of sign symptoms took 3 weeks (SD-3±1 weeks). Recovery was observed within 10 (9±2 day) days in 450 (60%) cases of using Ganciclovir. Short term complications such as pseudomembrane formation were found in 24% cases and corneal ulcer in 1 case. Superficial punctate keratitis (SPK) was found in 22% cases even after 3 months. Conclusion: Treating viral conjunctivitis without long term vision impairing sequel is a challenging job due to nonspecific presentation. Without specific features of bacterial or fungal conjunctivitis, patients of seasonal keratoconjunctivitis treated with Ganciclovir provide prompt resolution which save working hours of serving personnel. JAFMC Bangladesh. Vol 17, No 2 (December) 2021: 29-32